Design and Simulation Research on Digital Twin Task Driven Dynamic Control Model for Manufacturing Enterprises - Liang, Yongkang; Yu, Zhipu; Zhang, Ping (Informatica, 2025)
This article proposes a task driven dynamic operation management model based on digital twin technology from the perspective of manufacturing enterprises adapting to complex and diverse environments to improve management performance. It comprehensively utilizes various methods of information collection and fusion, real time status response feedback control, and task priority sorting to achieve a dynamic optimal structure that supports collaboration of multiple task operations. By using Anylogic multi agent simulation tool to model and simulate the model, multiple typical scenarios for task execution were set, and the model was evaluated for resource utilization, response time delay, and task scheduling quality. The experimental results showed that the model in this paper can effectively improve task execution efficiency (by 12.4%), task resource allocation and matching degree (by 17.8%), and task response timeliness (by an average time reduction of 23.5%), which can meet the requirements of intelligent production and business management.